2020
DOI: 10.1101/2020.03.21.001883
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of short-read RNA-Seq data to identify transcripts that can translate novel ORFs

Abstract: Identification of as of yet unannotated or undefined novel open reading frames (nORFs) and exploration of their functions in multiple organisms has revealed that vast regions of the genome have remained unexplored or 'hidden'. Present within both protein-coding and noncoding regions, these nORFs signify the presence of a much more diverse proteome than previously expected. Given the need to study nORFs further, proper identification strategies must be in place, especially because they cannot be identified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In more recent years, it was found that specific workflows can identify noncoding transcripts that can potentially translate intronic, intergenic and several other classes of ORFs (Fickett, 1994;Erady, Puntambekar and Prabakaran, 2020). A pipeline focused on genes coding for transcription factors was shown to increase isoform detection by an order of magnitude when compared to unenriched samples.…”
mentioning
confidence: 99%
“…In more recent years, it was found that specific workflows can identify noncoding transcripts that can potentially translate intronic, intergenic and several other classes of ORFs (Fickett, 1994;Erady, Puntambekar and Prabakaran, 2020). A pipeline focused on genes coding for transcription factors was shown to increase isoform detection by an order of magnitude when compared to unenriched samples.…”
mentioning
confidence: 99%